1990
DOI: 10.1037/0882-7974.5.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Tenacious goal pursuit and flexible goal adjustment: Explication and age-related analysis of assimilative and accommodative strategies of coping.

Abstract: Crises and critical life transitions activate 2 distinct but complementary modes of coping, (a) transforming developmental circumstances in accordance with personal preferences (assimilative tendency) and (b) adjusting personal preferences to situational constraints (accommodative tendency). Assimilative and accommodative tendencies were measured by a questionnaire comprising 2 independent scales (Tenacious Goal Pursuit and Flexible Goal Adjustment). Both scales predict high life satisfaction and low depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

68
882
3
25

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 887 publications
(978 citation statements)
references
References 31 publications
68
882
3
25
Order By: Relevance
“…Overall, the findings provide strong support for the dual-process model's assumptions 7 , and highlight the value of examining patterns and predictors of change in rehabilitation outcomes over time. 12 Interpreting adjustment as a dynamic, ongoing process could improve rehabilitation treatment and discharge planning.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Overall, the findings provide strong support for the dual-process model's assumptions 7 , and highlight the value of examining patterns and predictors of change in rehabilitation outcomes over time. 12 Interpreting adjustment as a dynamic, ongoing process could improve rehabilitation treatment and discharge planning.…”
Section: Discussionsupporting
confidence: 53%
“…8,9 This conceptual framework addresses the dynamics of goal management across the lifespan, delineating two basic self-regulatory modes that facilitate adjustment to loss and limitation. The assimilative (goal pursuit) mode is directed at actively trying to change unsatisfactory life circumstances or behaviour to correspond with goals and preferences, and enables maintenance of identity and purpose in adverse situations 7,10 .…”
Section: Fgamentioning
confidence: 99%
“…Higher scores signify greater tendency to engage in these adaptive strategies. The TGP and FGA scales have been used in various patient populations (25,26,36) and have demonstrated satisfactory reliability and validity (35). In the present study, Cronbach's alpha values of 0.81 and 0.64 were observed at T1 for the TGP and FGA scales, respectively.…”
Section: Methodssupporting
confidence: 55%
“…Alternatively, it has been suggested that older adults might adjust more readily to amputation than younger individuals, as they view changes in mobility and body image due to limb loss as undesirable but somewhat expected at their age (40). This view is reciprocated in the literature on selfregulation, which proposes that people come to rely increasingly on goal adjustment strategies as they grow older, which helps maintain a sense of well-being and satisfaction in the face of age-related losses and limitations (23,35). The limited capacity of amputation etiology and pain intensity to predict disability and QoL in the present study lends further support to the argument that the characteristics of an individual's health condition are insufficient in explaining the nature or extent of disability he or she experiences (4,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation